Dampak Pengumuman Covid-19 terhadap Perubahan Harga Saham, Volume Transaksi Saham dan Abnormal Return - Safitri, Nora; Nuraini, Eka; Yusnita, Raja Ria (Universitas muhammadiyah palembang, 2023)
The purpose of this study is to find out whether there are significant differences between stock prices, stock transaction volume and abnormal returns before and after the announcement of Covid-19 in the Food and Beverage Industry listed on the IDX. The population in this study were Food and Beverage companies listed on the IDX, using a purposive sampling technique so that the number of samples in this study were 14 companies. The analysis in this study was first by conducting a descriptive statistical test, then testing the normality and hypothesis testing. Hypothesis testing was carried out using the Wilcoxon signed rank test of differentials, by calculating stock price data, stock transaction volume and abnormal returns 31 days before and 31 days after the announcement. Based on the results of the analysis conducted, this study shows that there are significant differences in stock prices, stock transaction volume and abnormal returns. Where stock prices have decreased by 11%, stock transaction volume has increased by 24% and abnormal returns have increased by 49% after the announcement of Covid-19 in Indonesia.